Achieving useful data analytics for marketing: Discrepancies in information quality for producers and users of information - Manuel Morales-Serazzi; Óscar González-Benito; Mercedes Martos-Partal (BRQ Business Research Quarterly, 2023)
This study proposes as a key cause of the high failure rates in the implementation of analytical projects for marketing decisions, the discrepancy in the information quality (DIQ) perceived between producers (information technology [IT]) and users (marketing) of knowledge. Given that the DIQ between agents is a determining factor in the success of the ability to data analytics, this study focuses on examining this concept and its causes, specifically the resources related to data analytics that influence DIQ. The results of the surveys carried out with the IT and marketing managers of 95 companies in Spain, analyzed with a comparative methodological approach (dyadic), reveal the sources of the discrepancy, namely, the quality of the data, the technological capabilities, the talent, Chief Executive Officer (CEO) support, and alignment of the data plan with the marketing plan.
Keywords: M31; M15; D82; L10; 650; Quality information; data analytics capacity; discrepancies; alignment; big data